Uso dos solos, índices de vegetação e degradação na Apa das Onças-PB - Monteiro, Thereza Rachel Rodrigues (2013)
Caatinga Biome is little known and has been suffering severe environmental pressures, including in existing protected areas, being the use of geotechnologies of fundamental importance in the deepening of knowledge about that environment. The APA das Onças (São João do Tigre - Paraiba) was chosen for this study because of the diversity of existing ecosystems, associated with the presence of degradation that has systematically changing this area. This research aimed to apply different vegetation indexes to identify areas in APA that show high and low vegetation cover. Soon after this , we applied the NDVI index (Normalized Difference Vegetation) and SAVI (Soil ajusted Vegetation Index), noting which ones would fit the reality seen in the field survey, and subsequently it has identified Anthropization levels that has occurred in this conservation area to eventually create a basemap that guide the interventions for the protection of natural resources present. To achieve these goals were accomplished on-site visits and digital processing of satellite images Lansat 5, TM sensor , for the years 1989, 1992 and 2010 for the identification of landscape units and Anthropization levels. The digital processing of images, it was possible to perform the atmospheric correction, radiance and reflectance in ERDAS 9.3 images to generate the vegetation indexes NDVI and SAVI, and subsequently conference in Excel 2007 spreadsheet. Based on NDVI and SAVI thematic maps generated in Arcgis 9.3, it was identified spatially what would best represent the reality found. The SAVI showed better the biomass reality present in the APA , while the NDVI did not distinguish reliably targets on the surface, confusing which would be degraded area and Caatinga Hiperxerophyle. With SAVI was possible to create a base map of thematic maps of landscape units of the APA , with the following classes : Environmental Degradation , Caatinga Hiperxerophyle , Caatinga hypoxerophytic , Mata Serrana and Brejo de Altitude. In spatio-temporal analysis in images 1989 , 1992 and 2010, it was perceived increase in degraded areas or who have suffered some kind of change in vegetation due to land use for agricultural purposes or due to extraction. The data found indicates the urgent need for the development of intense surveillance actions to curb the changes , while activities should be encouraged to use existing resources on a sustainable basis.